2017
DOI: 10.1007/s00127-017-1477-7
|View full text |Cite
|
Sign up to set email alerts
|

What drives the relationship between combat and alcohol problems in soldiers? The roles of perception and marriage

Abstract: Our results demonstrate that the perception of combat experiences as traumatic may be a greater contributor to adverse outcomes, such as alcohol problems, than mere combat exposure. They also demonstrate the importance of marital satisfaction as a resiliency factor, particularly at the highest levels of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
(64 reference statements)
0
21
1
Order By: Relevance
“…There is robust evidence in the literature demonstrating the association between deployment and/or combat exposure and alcohol misuse in military populations (Green et al, 2014, Hoge et al, 2006, Bray and Hourani, 2007, Milliken et al, 2007, Wright et al, 2012, Jacobson et al, 2008, Seal et al, 2011, Vest et al, 2018, Hoopsick et al, 2018). While rates of alcohol misuse among service members are generally high, particularly for binge and heavy drinking (Bray et al, 2013), some evidence suggests that deployment and/or combat may contribute to an increased risk of alcohol misuse as a means of self-medication in response to war-related psychological sequelae, such as post-traumatic stress disorder (PTSD) and depression (Wright et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is robust evidence in the literature demonstrating the association between deployment and/or combat exposure and alcohol misuse in military populations (Green et al, 2014, Hoge et al, 2006, Bray and Hourani, 2007, Milliken et al, 2007, Wright et al, 2012, Jacobson et al, 2008, Seal et al, 2011, Vest et al, 2018, Hoopsick et al, 2018). While rates of alcohol misuse among service members are generally high, particularly for binge and heavy drinking (Bray et al, 2013), some evidence suggests that deployment and/or combat may contribute to an increased risk of alcohol misuse as a means of self-medication in response to war-related psychological sequelae, such as post-traumatic stress disorder (PTSD) and depression (Wright et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Years of military service included the total years of active duty service (if applicable) and years of Reserve/Guard service. Marital satisfaction has been shown to be a strong protective factor against the effects of military‐related stress on poor mental health (Vest et al, ) and alcohol problems (Vest et al, ) among Reserve/Guard soldiers. We used the Marital Adjustment Test (Locke & Wallace, ), a 15‐item Likert‐based scale, to assess marital satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…Service members are at greater risk for problems with alcohol and other substances than civilians (Bray, Brown, & Williams, ; Green, Beckham, Youssef, & Elbogen, ; Hoopsick, Fillo, Vest, Homish, & Homish, ; Jacobson et al, ; Milliken, Auchterlonie, & Hoge, ; J. L. Thomas et al, ). Further, there is an abundance of literature demonstrating the effects of deployment on mental health and substance use outcomes among service members (Bray & Hourani, ; Hassija, Jakupcak, Maguen, & Shipherd, ; Jacobson et al, ; Larson, Mohr, Jeffery, Adams, & Williams, ; Milliken et al, ; Renshaw, Rodrigues, & Jones, ; M. M. Thomas, Harpaz‐Rotem, Tsai, Southwick, & Pietrzak, ; Vest, Heavey, Homish, & Homish, ; Vest, Homish, Hoopsick, & Homish, ). Thus, negative social interactions or experiences may contribute to even greater risk for substance use among this already high‐risk group.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, marital satisfaction has not been examined as a protective factor that may reduce the incidence of post-deployment drug use among service members. However, recent research demonstrated that marital satisfaction was a strong resiliency factor in protecting against post-deployment anger, anxiety, depression, and PTSD among male USAR/NG soldiers (Vest et al, 2017), and has also been shown to protect against the effects of combat exposure on alcohol problems among this population (Vest et al, 2018).…”
Section: Resiliency Factorsmentioning
confidence: 99%